Low power bandgap voltage references - Zhou, Wei (2015)
Bandgap voltage reference plays an important part in many circuits such as data convertors, voltage regulators, and oscillators. It provides a relatively constant voltage to other circuit blocks. In this project, two bandgap voltage references are designed using Global Foundry 0.18 μm CMOS process and simulated using BSIM3v3 model provided by Cadence software. The non-amp-based bandgap voltage reference works under supply voltage of 1.2 V with total power consumption of 4.272 μW, generating 0.966 V output voltage under standard simulation conditions with power supply rejection ratio of -32.89 dB at 1 kHz and average temperature coefficient of 29.37 ppm/˚C. The amp-based bandgap voltage reference works under supply voltage of 1.8 V with total power consumption of 11.79 μW, generating 0.963 V output voltage under standard simulation conditions with power supply rejection ratio of -42.84 dB at 1 kHz and average temperature coefficient of 15.97 ppm/˚C.